Keamanan Cyber dalam Menghadapi Tantangan Ancaman Masa Depan di Universitas Bhayangkara Jakarta Raya - Hafidz Prasetyo; Iib Ibrahim; Jeremia; Moh Milhan Hijrah Moelyana; Zaidan Muhammad Abid (Journal of Informatic and Information Security, 2024)
The development of information technology has had a major impact on many aspects of life, including higher education. Bhayangkara University faces various challenges related to cybersecurity such as the risk of phishing, malware, ransomware, and data leaks that can disrupt academic and administrative systems. The purpose of this study was to assess how aware and knowledgeable students are about cybersecurity issues, recognize existing threats, and provide strategic suggestions to improve data protection in the campus area. The study involved 40 participants from Informatics majors at Bhayangkara University through a questionnaire. The findings show that the majority of students have a high awareness of the importance of cybersecurity, although there are still shortcomings in the implementation of best practices, such as the use of strong passwords and verification of email authenticity. This study suggests implementing measures such as periodic training, strengthening digital systems, and creating campus policies to comprehensively improve cybersecurity. The results of this study are expected to assist in the development of more effective digital security policies in higher education institutions.